The mouse mutation “thrombocytopenia and cardiomyopathy” (trac) disrupts Abcg5: a spontaneous single gene model for human hereditary phytosterolemia/sitosterolemia - Chase, Thomas H. (American Society of Hematology, 2010)
The spontaneous mouse mutation “thrombocytopenia and cardiomyopathy” (trac) causes macrothrombocytopenia, prolonged bleeding times, anemia, leukopenia, infertility, cardiomyopathy, and shortened life span. Homozygotes show a 20-fold decrease in platelet numbers and a 3-fold increase in platelet size with structural alterations and functional impairments in activation and aggregation. Megakaryocytes in trac/trac mice are present in increased numbers, have poorly developed demarcation membrane systems, and have decreased polyploidy. The thrombocytopenia is not intrinsic to defects at the level of hematopoietic progenitor cells but is associated with a microenvironmental abnormality. The trac mutation maps to mouse chromosome 17, syntenic with human chromosome 2p21-22. A G to A mutation in exon 10 of the adenosine triphosphate (ATP)–binding cassette subfamily G, member 5 (Abcg5) gene, alters a tryptophan codon (UGG) to a premature stop codon (UAG). Crosses with mice doubly transgenic for the human ABCG5 and ABCG8 genes rescued platelet counts and volumes. ABCG5 and ABCG8 form a functional complex that limits dietary phytosterol accumulation. Phytosterolemia in trac/trac mice confirmed a functional defect in the ABCG5/ABCG8 transport system. The trac mutation provides a new clinically significant animal model for human phytosterolemia and provides a new means for studying the role of phytosterols in hematologic diseases and testing therapeutic interventions.